PENGARUH FLUKTUASI NILAI TUKAR USD, JPY, CNY TERHADAP RUPIAH PADA PERKEMBANGAN EKSPOR DAN IMPOR INDONESIA TAHUN 2013 – 2019 - Hastasari, Ratih; Suharini, Suharini; Triningsih, Triningsih (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This research was being conducted based on the condition of international trade and the condition of Indonesian economic at the macro level. The researcher chose to use dependent variables as to exsport(Y1) and import(Y2) activities. In the meantime independent variables used is the exchange rate that is used by the biggest amount of export based on country destination. That current exchange are CNY(X3) from Tiongkok, JPY(X2) from Japan, and USD(X1) from United States of America. The result of the research with dependent variable of export showed that the USD and JPY partially have significant influence to exsport activities. Meantime the CNY variables has not significant influence to export activities. The result of the research with dependent variable of import showed that the trhree variables partially have not significant influence to import activities.